Sisters in The Mirror : A History of Muslim Women and The Global Politics of Feminism - Shehabuddin, Elora (Oakland, California : University of California Press, 2021)
Taking a transnational approach, this book challenges the belief that the Muslim world is unrelentingly antifeminist. The author challenges assumptions about inevitable civilizational antagonism between the "West" and the "Muslim world," a notion that has become increasingly popular in recent decades, and of a lag in the emergence of feminism in the latter. While it shouldn't be controversial to insist that male bias and privilege are present in Western as well as in Muslim-majority societies, it is more difficult to show how and why efforts to improve women's lives in even these geographically distant parts of the world have long been interconnected and interdependent. Sisters in the Mirror is a feminist story about how changing global and local power disparities-between Europeans and Bengalis, between Brahmos, Hindus, and Muslims within Bengal, between feminists of the global North and South, and between Western and Muslim feminists-have shaped ideas about change in women's lives and also the strategies by which to enact change. With the lasting shift in the balance of economic, political, and military power between Muslim and Euro-American nations toward the latter since the eighteenth century, Muslim advocates for women's rights have had to define their agendas for reform in the shadow of Western imperial and economic power. The stories in this book show that no society has a monopoly on ideas about justice and fairness (in the matter of women's or any other group's rights) or, for that matter, on male bias, violence, and injustice; no community is isolated or pure; and people everywhere are enriched by open-minded encounters with people who eat, dress, and pray differently, or don't pray at all.
Keywords: Feminism--India--Bengal.; Muslim women--India--Bengal--History.; Globalization--Religious aspects--Islam.; Muslim women--Political activity